Acute and overuse injuries in European junior badminton players - Petrinovic, L.; Trost Bobic, T.; Ciliga, D. (World Badminton Federation, 2016)
Badminton is an individual, non-contact sport requiring jumps, lunges, quick changes of direction and rapid arm movements from a wide variety of postural positions. The physical demands of badminton suggest that acute injuries to the limbs may be a frequent occurrence (Yung et al., 2007). However, overuse injuries of the back, shoulder, lower leg and knee may also be present (Fahlström , Lorentzon & Alfredson, 2002; Fahlström et al., 2006). Even though there are publications reporting badminton players injuries, knowledge so far is mostly based on studies about acute injuriesof recreational players or elite top-level professional athletes (Fahlström & Soderman, 2007). The frequency, location and severity of injuries in junior badminton players remains poorly understood. To plan effective preventive training for young badminton players, their specific epidemiology of injuries must be taken in consideration. The main aim of this study was to investigate the frequency, location and severity of acute and overuse injuries in junior badminton players, aged under 19 years old (17-19 years). The most common sites of injury were also studied. The correlation between their anthropometric status, foot alignment and injury was examined. In addition, differences in explosive strength between the injured and non-injured junior badminton players was evaluated.